Assessment and treatment of older adults : a guide for mental health professionals - Hinrichsen, Gregory A., 1951- (American Psychological Association, 2019)
"The book is a broad overview for those mental health practitioners without prior aging background who are serving some older adults in clinical practice. It is a primer for those who want to learn the professional lay of the land in geropsychology. The book is also informed by many years of experience in conducting introductory mental health and aging continuing education workshops for psychologists, social workers, and related disciplines. It has seven chapters. The first two chapters examine attitudes toward aging and basic facts about and perspectives on the aging process. Chapters three and four are general overviews of issues in assessment and treatment of older clients. Chapter five reviews assessment and treatment of depression and anxiety and Chapter six discuss assessment and treatment of cognitive impairment and problem alcohol use and prescription drug misuse. Chapter seven summarizes key themes of the book and offers practical recommendations for those interested in further building knowledge and skills relevant to geropsychology."--Preface. (PsycINFO Database Record (c) 2019 APA, all rights reserved)